Factors Associated with the Nutritional Status of Pregnant Women in Banjarmasin City: A Cross-Sectional Analytical Study - Ari Widyarni; M. Bahrul Ilmi; Netty Netty; Elsi Setiandari Lely Octaviana; M. Febriza Aquarista; Edy Ariyanto; Husnul Khatimatun Inayah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: The nutritional status of pregnant women is a critical indicator of maternal and fetal health. Chronic Energy Deficiency (CED) during pregnancy increases the risk of obstetric complications, low birth weight, stunting, and contributes indirectly to maternal mortality. Indonesia continues to report one of the highest maternal mortality ratios in Southeast Asia. This study aimed to analyze factors associated with the nutritional status of pregnant women in Banjarmasin City. Methods: This analytical cross-sectional study involved 100 pregnant women selected using accidental sampling. Nutritional status was assessed based on mid-upper arm circumference (MUAC), with MUAC <23.5 cm indicating CED. Independent variables included maternal knowledge, parity, maternal age, and toothbrushing habits. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses with the Chi-Square test. Effect sizes were reported as prevalence ratios (PR) with a significance level of 0.05. Results: The prevalence of CED among pregnant women was 52%. The majority of respondents had low levels of knowledge (59%), risk parity (88%), risk maternal age (63%), and bad toothbrushing habits (58%). Bivariate analysis showed significant associations between maternal knowledge (PR=2.08; p=0.001), maternal age (PR=1.59; p=0.012), and toothbrushing habits (PR=1.95; p=0.000) with nutritional status. Parity was not significantly associated with nutritional status (p=0.076). Conclusion: Maternal knowledge, age, and toothbrushing habits were significantly associated with the nutritional status of pregnant women in Banjarmasin City. Strengthening nutrition education and healthy lifestyle behaviors through Posyandu services and antenatal education programs is essential to prevent CED and improve maternal and fetal health outcomes.